PENGARUH KEBERADAAN AKAR ADVENTIF DAN MEDIA TANAM TERHADAP PERTUMBUHAN STEK CABANG BAMBU BETUNG (Dendrocalamus asper Schult Backer ex Heyne) Influence of Adventitious Roots and Planting Media on Growth of Branch Cutting of Betung Bamboo - Yan Eka Prasetyawati; Cahyo Wibowo; Sri Wilarso Budi R. (Jurnal Silvikultur Tropika, 2018)
The need of bamboo raw materials, betung bamboo for instance, keeps increasing in line with the rising rate of population growth and science development. Therefore, stands of bamboo clumps with sustainable productivity and quality, are absolutely required. One of betung bamboo’s characteristics is presence of adventitious roots in branches of bamboo culm. The problem is that many of such branches often have dry adventitious roots which are brown in color. Based on such condition, research of the effect of presence of dry adventitious roots, need to be conducted, as well as the effect of growth media, on the growth of bamboo branch cuttings. The research objective is to examine the effect of bamboo branches with dry adventitious roots and planting media on growth of betung bamboo’s branch cuttings. The media used are soil, rice husk charcoal and compost. The experiment which used factorial RAK design showed that planting media significantly affected leaf numbers, whereas adventitious roots had significant effect on all measured parameters, including shoot length, shoot numbers, leaf numbers, oven dry weight of roots, and survival percentage. Media with the highest leaf numbers were mixture of soil and rice husk charcoal.Keywords: adventitious root, Dendrocalamus asper, planting media, branch cutting